Active Learning Strategies In Improving Optimal Learning Among Arabic Education Students - A. Zuhruddi Hadi Saputra; Zamakhsari Zamakhsari; Eva Latipah (Universitas Muhammadiyah Ponorogo, 2025)
This article aims to determine the application of active learning strategies in teaching Arabic language planning courses to Arabic language education students at UIN Sunan Kalijaga Yogyakarta, and to analyze the effectiveness of active learning strategies in increasing student engagement and critical thinking skills. This study uses a qualitative approach with a descriptive field research type. The research subjects were Arabic Education students in class D in their third semester. Data collection included observation, interviews, and documentation to obtain data on implementing active learning strategies and student responses to the learning process. This study shows that the application of active learning strategies using small group discussion and question-and-answer methods created an interactive learning atmosphere. This strategy also improved students' understanding of the course and encouraged them to solve problems actively. However, there were obstacles such as a lack of preparation and confidence among students. Active learning can be an alternative learning strategy in higher education to optimize student potential.